Natural Deep-Seated Hydrogen Resources Exploration and Development: Structural Features, Governing Factors, and Controls - Vidavskiy, Vitaly; Rezaee, Reza (2022)
The interest towards natural, or subsurface, sources of hydrogen is gaining momentum among the scientific and the industrial communities: the former is anxiously looking for the guidelines to de-risk its exploration and development operations, while the latter is trying to match the (mainstream) concepts with this new commodity physical and geochemical properties, which are quite different from the conventional ones (hydrocarbons, etc.). Apparently, it is time for new, alternative concepts capable of resolving the existing discrepancies and offering plausible solutions for removing the obstacles currently existing in the way of this new industry. Currently, the goal is formalized as (i) analyze the vast dataset existing for natural hydrogen shows, and (ii) to provide practical recommendations for natural hydrogen resources’ exploration, aiming commercial sources discovery and exploitation. In this lieu, this research attempts to identify and classify the principles of natural hydrogen provenance and distribution within the lithosphere, as well as its manifestations on the surface. While explaining the scientific basics of the subject in commonly acceptable terms, the authors bring the theoretical part of the discussion to the bare minimum, at the same time concentrating on the practical implications and outcomes. This study analyzes the majority of known natural hydrogen cases in Australia and compares them with several examples known around the globe. The main controls, such as structural, stratigraphical, lithological, geochemical, and tectonic elements are reviewed and ranked. Several commonly accepted conceptual points are confirmed, while others are questioned and debated. The most typical patterns are outlined and interpreted; the practical leads resulting from these patterns are discussed. For the main outcome, the paper attempts offering the well-founded and logically verified scientific basis for the players to get their next steps coherent and reasonably justified. In conclusion, the authors provide more clari